Salinity Reduction of Sarawak Brackish Peat Water Sources by Utilizing Electrocoagulation Treatment System with Enhanced Faradaic Efficiency - Nazeri, Abdul Rahman; Calvin, Jose Jol; Allene, Albania Linus; Arif, Parabi; Astisza Syahla Ludmilla, Parabi; Anthonette, James; Nur Syazwa, Shamsol; Sebastian Belun, John; Elyza Farhana, Kushairy; Airul Azhar, Jitai; Dayang Fadhilatul Aisyah, Abang Abdul Hamid (Universiti Tun Hussein Onn (UTHM), 2025)
Brackish peat water in Sarawak’s rural coastal areas poses a serious treatment challenge due to changing salinity and high organic matter. Although electrocoagulation shows potential as a treatment method, its performance and reliability for this specific water source have yet to be thoroughly investigated. As such, this study aims to investigate the Faradaic efficiency of electrocoagulation treatment system in reducing salinity levels of Sarawak brackish peat water. Correspondingly, the objectives of this study include brackish peat water salinity characterization, Tafel analysis of aluminium corrosion, evaluating the effects of seawater percentages and applied voltages on Faradaic efficiency, and water quality analysis. Additionally, this study examines the salinity levels of Sarawak brackish peat water and its effect on aluminium corrosion using Tafel analysis followed by electrocoagulation treatment. The treatment efficiency was assessed through Faradaic efficiency and water quality tests with results compared to the Malaysia National Water Quality Standard. Subsequent, this study has found a linear correlation between salinity and seawater percentage, with salinity peaking at 19,300 mg/l at 100% seawater percentage. Tafel analysis also demonstrated that high seawater percentages could increase aluminium electrode corrosion owing to corrosion potential (Ecorr) reaching -1,256.82 mV and corrosion current density (Icorr) rising to 308.607 μA at 100% seawater. This study has also reported an optimal Faradaic efficiency of 95.63% was achieved at 10 V and 30% of seawater percentage. Moreover, the electrocoagulation system effectively reduced salinity levels which deemed suitable for domestic consumption under Class I of Malaysia National Water Quality Standards (NWQS). Overall, this study demonstrated the potential of electrocoagulation system as a sustainable system for salinity reduction in Sarawak brackish peat water at an optimum Faradaic efficiency.